Influence of Cadmium, Zinc, and Lead on Growth, Trap Formation, and Collagenase Activity of Nematode-Trapping Fungi - Rosenzweig, W. D. (1980)
Growth and morphogenesis of seven species of nematode-trapping fungi and the activity of a collagenase produced by Arthrobotrys amerospora were measured in the presence of various concentrations of divalent cadmium, zinc, or lead. In general, growth varied with species and was dependent on the metal present and the concentration at which it was tested. Cadmium was found to exhibit the greatest toxicity followed by zinc and lead, respectively. In most cases, inhibition of growth was directly correlated with a decreased capacity to form traps. However, in a few cases, trap formation was inhibited either more or less than was growth. The activity of the collagenase was less sensitive than was growth or trap formation to heavy-metal inhibition.